Effect of fast Surya Namaskar versus aerobic dance on cardiorespiratory fitness in children aged 10-13 years at the end of 4 weeks: a comparative study - Patil, Komal; Afle, Gauri (International Journal Of Community Medicine And Public Health, 2025)
Background: The COVID-19 pandemic led to a major reduction in physical activity (PA) among children, with average PA levels decreasing from 540 to 105 minutes per week. This decline was associated with increased sedentary behavior and reduced cardiorespiratory fitness (CRF), measured by VO2max. Fast Surya namaskar and aerobic dance, both high-intensity aerobic exercises, are known to improve CRF. This study aimed to compare the effects of fast Surya namaskar and aerobic dance on CRF in children aged 10-13 years. Methods: A comparative two-group pretest-posttest study was conducted from March 2024 to March 2025 on 120 healthy children aged 10-13 years from schools in and around Pune. Participants were randomly divided into two groups of 60 each using simple random sampling. Group A performed fast Surya namaskar and group B performed aerobic dance, for three alternate days per week for four weeks. Pre- and post-intervention VO2max and BMI were recorded. Data were analyzed using paired and unpaired t-tests with significance set at p<0.05 and a 95% confidence interval. The sample size was calculated from a pilot study with a 95% confidence level and 80% power. Results: Both groups showed significant improvements in VO2max and BMI (p<0.0001). Group A’s VO2max increased from 38.64±3.10 to 40.60±3.79, and group B’s from 38.82±3.06 to 41.22±3.19. BMI decreased significantly in both groups. Conclusions: Both fast Surya namaskar and aerobic dance improve CRF in children, with aerobic dance showing slightly greater improvement.